Can digital farming technologies enhance the willingness to buy products from current farming systems? - Rolf Wilmes; Gabi Waldhof; Peter Breunig (PLOS ONE, 2022)
While current global agriculture allows for efficient food production, it brings environmental disadvantages, which resulted in a lack of public acceptance. Digital technologies (e.g., technologies that enable precision agriculture) have been suggested as a potential solution to reconcile environmental sustainability and yield increases. By embedding digital technologies into holistic farming system visualized through mission statements, this study tests the effect of different intensities of digitization, as well as environmental arguments on the willingness to buy food produced by farms in Germany. We use a 4 x 4 repeated measure experimental design surveying a representative sample of 2,020 German citizens recruited online. Our research framework captures the farming system (comparing low intensity of digitalization for a small or organic farm and low, medium, and high intensity of digitalization for large or conventional farms) and environmental arguments (comparing no arguments, and altruistic, egoistic, and biospheric arguments). The results show a negative effect of digital technologies on willingness to buy. However, this relationship turns positive when introducing environmental arguments. Furthermore, there is a moderation effect for respondents' attitudes towards technologies that varies depending on whether altruistic, egoistic, or biospheric concerns were stated. The results indicate that digital technologies can increase willingness to buy products from both large and conventional farms, but not to the level of small farms and organic farms.
Keywords: 330